Open-Circuit End Effect of Microstrip Line Configuration in Plasma Medium - Prem Bhushan Mital (Active and Passive Electronic Components)
The extension in length for open microstrip configuration in plasma media is determined using spectral domain technique under quasi static approach [1, 2]. The results were verified by modifying Hammerstad equation for plasma media. Good agreement is found between the two results.